TELAAH KITAB SUNAN IBN MAJAH - Achmad Lubabul Chadziq (Institut Keislaman Abdullah Faqih Gresik, 2020)
Abstrak: The attention of hadith scholars in maintaining the authenticity of the hadith of Rasullullah SAW is proven by their ijtihad in seeking and researching it, it is not uncommon for them to carry out transnational ilmiyah with means of transportation that are full of limitations which eventually produce the Kutub al-Ushul al-Sittah (six main books of hadith) and other spectacular hadith books. Among the books of the Sunan, the book of Sunan Ibn Majah, including the most pros and cons among hadith scholars, besides because it contains authentic hadiths, hasan, and many da'if hadiths, this book also collects many zawaid hadiths that are not collected in the books. the previous Hadith book (Kutub al-Ushul al-Khamsah), so it is questionable when it is included in the Kutub al-Ushul al-Sittah. The majority of hadith scholars include the book Sunan Ibn Majah in the row of the Kutub al-Ushul al-Sitta, because of the thousands of zawaid hadiths contained in it, it turns out that half of them are valid and hasan status worthy of evidence.Keywords: Sunan Ibn Majah, Kutub al-Ushul al-Sittah.